2020
DOI: 10.1021/acsomega.0c01023
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Swelling Potential Evaluation of Moringa oleifera Gum/Poly(vinyl alcohol) Hydrogels as a Superabsorbent

Abstract: Synergistic use of superabsorbent hydrogels has vital contribution to the daily life. This work gives an account of a facile approach to synthesize superabsorbent hydrogels based on Moringa oleifera gum and polyvinyl alcohol cross-linked with borax. Fourier transform infrared, X-ray diffraction, and scanning electron microscopy were employed to characterize the structure, crystallinity, and surface morphologies of the samples. The cross-link density, swelling ratio, reswelling, water ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 37 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…In 0.9% NaCl, the maximum swelling capacity is 78 g/g when the swelling time is 30 min. In comparison with the research works reported in the literature, the superabsorbent composite prepared in this study possessed faster swelling rate and higher swelling capacity 8,34,35 …”
Section: Resultsmentioning
confidence: 52%
“…In 0.9% NaCl, the maximum swelling capacity is 78 g/g when the swelling time is 30 min. In comparison with the research works reported in the literature, the superabsorbent composite prepared in this study possessed faster swelling rate and higher swelling capacity 8,34,35 …”
Section: Resultsmentioning
confidence: 52%
“…Montheil introduced a “biocompatible catalysis” approach for bioink formation using aqueous solutions in which silylated hydroxypropylmethyl cellulose crosslinking was catalyzed by NaF and/or glycine [ 166 ]. “Catalyst-free” superabsorbent hydrogel synthesis in water was demonstrated by Ahmad et al via crosslinking Moringa oleifera gum and polyvinyl alcohol with borax [ 167 ]. As a more biocompatible alternative to the Irgacure 2959 photoinitiator, Bui et al synthesized a catechol-functionalized hydrogel using dopamine as a photoinitiator to polymerize sulfobetaine methacrylate and BIS in Tris buffer.…”
Section: Synthesis Strategies To Achieve Target Propertiesmentioning
confidence: 99%
“…where D and D 0 are the same as for Eqn (2). The release of ofloxacin from the dry loaded gel was measured by placing it in phosphate buffer (500 mL, pH 7.4) at 37 °C, simulated blood medium, for 61.5 h with constant stirring.…”
Section: Drug Loading and Releasing Measurementsmentioning
confidence: 99%
“…Superabsorbent hydrogels are hydrophilic, three‐dimensional networks that can easily swell with water or other liquids up to thousands of times their own dry weight while maintaining their physical dimension structures. Because of their exceptional properties, they are widely used in various industrial applications such as agriculture, foods, personal care products, cosmetics, medicines and other biomedical applications 1–3 . Hydrogels that respond to external conditions such as heat, pH, chemical environments, etc., are often referred to as smart hydrogels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation